Development Of Counseling Guidance Management For Career Exploration of Class IX Students at Madrasah Tsanawiyah - Rholanjiba, Sefti; Riswandi, Riswandi; Z., Ranni Rahmayanti; Nurwahidin, Muhammad (UNDIKMA, 2024)
The low implementation of counselling services also affects the low interest of students who feel the presence of counselling guidance is important. Guidance and counselling should be an important part of education that aims to help students achieve independence in their lives and can carry out developmental tasks covering personal, career, learning and social aspects. This study aims to determine the effectiveness of developing a counselling management module for exploring the career potential of students in junior high school. The development research method used in this research uses the ADDIE approach (Analysis, Design, Development, implementation and Evaluation). The results of research on the development of counseling guidance modules on career exploration of class IX MTSN 1 Pesawaran Lampung students, can be implemented with a recapitulation of the results of product development validation with a result of 89.6% with a very feasible category, the effectiveness of module development with a score of 94.6% with a very feasible category, for the application of the module getting 95.5% high quality, 80.1% very high category, and 33 or 24.2% moderate category on the implementation of the development of counseling guidance management modules for students' career exploration.